Sosialisasi Perizinan Berusaha Berbasis Risiko dan Merek Terhadap Pelaku Usaha Mikro Desa Bunder Pademawu Pamekasan - Hasanah, Uswatun; Djulaeka, Djulaeka; Suastuti, Eny (Jurnal Ilmiah Pangabdhi, 2023)
Based on the previous research, it is known that the micro-enterprises in Bunder, Pademawu, Pamekasan, do not yet have a business license. Moreover, since 2021 there has been a new licensing regulation known as a risk-based permit, so it is necessary to provide literacy on norms, standards, procedures, and criteria in obtaining such permits. In addition, the products of this micro-enterprises do not yet have a trademark. To help overcome these problems, socialization was carried out to micro business actors. The socialization is related to risk-based business licensing and intellectual property rights-based product registration. This activity consists of identifying potentials and problems as well as licensing and trademark socialization activities. This socialization was carried out at the Bunder Village Hall, attended by about 25 micro-enterprises and attended by employees of the Cooperatives and Micro Business Office, Village Heads and Apparatus, as well as BUMDes Management. At the end of the socialization activity, assistance is provided to micro-enterprises so that they can register for a license to obtain a Business Identification Number and micro business actors obtain proof of trademark registration at the Ministry of Law and Human Rights.